Implementasi Kebijakan Penyelenggaraan Pendidikan Kesetaraan Di Kabupaten BanyuwangI Provinsi Jawa Timur - Darmanto, Aldy; Hasan, Fuad; Himmah, Irliana Faiqotul (Learning Community : Jurnal Pendidikan Luar Sekolah, 2023)
The purpose of this research is to describe how equality education policies are implemented in Banyuwangi Regency. The research method used in this research is to use a descriptive research method with a qualitative approach. The results of the study explained that the implementation of education policies had gone well through several stages, namely 1) Forum Group Discussion, 2) Socialization, 3) Recruitment Patterns, 4) Implementation, 5) Evaluation. The obstacles that occur during the implementation process are 1) Lack of enthusiasm by the learning community to participate in the learning process, 2) Limited learning support facilities, 3) Lack of mastery of information technology, and 4) Lack of concern for some stakeholders about the importance of equality education. In addition, there are several factors that support the implementation of the policy, namely 1) Educators, 2) Facilities and Infrastructure, 3) Funding, 4) Banyuwangi District Government Support, and 5) Equality Education Program Innovation. The efforts made by the Regional Government to overcome obstacles to policy implementation are 1) Coordination, 2) Communication, 3) Cooperation